Analysis of Civil Servant Neutrality in Palembang Through Discourse Network Analysis and Social Network Visualization (GEPHI) - Zainal Prima Putra; Alamsyah Alamsyah; Raniasa Putra; M Nur Budiyanto; M. Husni Thamrin (Politeknik Siber Cerdika Internasional, 2026)
Background: Civil servant (ASN) neutrality is often viewed merely as a matter of administrative and legal compliance; however, in practice, it involves complex narrative dynamics among various policy actors in the public sphere. Objective: This study aims to map the policy discourse structure of ASN neutrality in the 2024 Palembang local election and identify key actors and their underlying patterns of interest. Methods: Using a mixed-methods approach through Discourse Network Analysis (DNA) and social network visualization via Gephi software, this study analyzed 56 statements from 40 relevant policy actors. Results: The results reveal a fragmented discourse network (96 nodes; density = 0.05; modularity ≈ 0.87), with consensus concentrated around law enforcement and disciplinary sanctions. Bawaslu RI emerged as the actor with the highest degree centrality (degree ≈ 15 connections), dominating the oversight narrative alongside regulatory agencies, whereas civil society groups and ASNs exhibited lower centrality scores and remained peripheral in the policy debate. Conclusion: The study concludes that strengthening bureaucratic ethical education and fostering more inclusive cross-sectoral collaboration are essential to safeguarding bureaucratic integrity from practical political intervention.